Systematic Study of Risk-Based Medical Waste Management in Teaching Hospitals - Nawra Madzura; Rasmi Zakiah Oktarlina; Ratri Mauluti Larasati; Novita Carolia (Sean Institute, 2026)
Background: Teaching hospitals are highly complex due to the integration of service, education, and research functions, resulting in a larger and more varied volume of hazardous medical waste. A risk-based management approach is crucial to mitigate occupational health impacts and environmental pollution. Objective: This systematic review aims to analyze risk-based medical waste management practices, operational indicators that determine waste generation, and control strategies in teaching hospitals. Methods: This study used the Systematic Literature Review (SLR) method following the PRISMA protocol. Article searches were conducted in Scopus, ScienceDirect, and Taylor & Francis databases for publications from 2021–2026, resulting in 9 primary articles for synthesis. Results: Risk analysis based on Failure Mode and Effects Analysis (FMEA) showed that the waste transfer stage and direct exposure to body fluids were critical points with the highest risks. In the laboratory area, risks were dominated by chemical and ergonomic hazards. Medical waste generation was strongly correlated with hospital operational indicators such as Bed Occupancy Rate (BOR), Bed Turnover Rate (BTOR), duration of hospitalization, and infection rates (HAIs). For final treatment, incineration is the optimal choice based on a multi-criteria decision-making (MCDM) for large capacities, while a combination of chemical disinfection and pyrolysis offers the most environmentally friendly option based on a Life Cycle Assessment (LCA). Human factors, particularly training frequency, have been shown to be a key predictor of staff sorting compliance. Conclusion: Medical waste management in teaching hospitals requires an integrated management system that combines periodic risk assessments, sustainable treatment technologies, and continuous staff training.